Sternal exocrine glands in Neotropical Social Wasps - da Silva, Marjorie [UNESP]; Noll, Fernando Barbosa [UNESP]; Billen, Johan (Springer Nature, 2020)
A great diversity of exocrine glands is found in social insects. The main social function of exocrine glands is the production of pheromones, which are related to the maintenance of social organization of the colony, as interactions of dominance, maintenance of queen status, recruitment for food, search for nesting sites, defense, and reproductive behaviors, among other aspects. The exocrine glands can be classified into two types (class 1 and class 3) according to their structural arrangement. Some of them are common to all social insects, occurring in males and females (e.g., mandibular and salivary glands). Others are characteristic of a taxon, as the van der Vecht and Richards glands, found only in vespids of the Vespidae family. An overview about the structure, location, and, whenever possible, function of the exocrine glands of Neotropical social wasps is presented here. Future studies considering large and more detailed morphological analyses, together with information on the chemical aspects of the produced secretions, are desirable for a broader understanding of the function of the pheromones produced by the exocrine glands in the social wasps.
Keywords: Behavior; Class 1; Class 3; Pheromones; Polistinae; Swarming